THE LINGUISTIC, CULTURAL AND COMMUNICATIVE ASPECTS OF TRIBAL LANGUAGES (Ideal Journal of Multidisciplinary Research, 2026)
Tribal languages represent a crucial part of the world’s linguistic diversity and cultural heritage. They carry unique phonological, morphological, and syntactic features that distinguish them from national and widely spoken languages. Beyond their linguistic structure, tribal languages encode social norms, traditions, and values, serving as a medium for storytelling, oral literature, and ritual practices. This study investigates the linguistic characteristics of tribal languages, their cultural significance, and their communicative functions. Drawing on examples from various tribal languages worldwide, the research demonstrates that these languages are not only tools for daily interaction but also repositories of collective memory, identity, and cultural knowledge. Understanding tribal languages contributes to the preservation of linguistic diversity and the promotion of intercultural understanding.
Keywords: tribal languages, linguistic features, oral tradition, cultural heritage, communicative function, sociolinguistics.